The Legal Protection for Independent Practicing Doctors in Providing Telemedicine Services to Patients - Kartika, Kartika; Andika, Andika (Soepra Jurnal Hukum Kesehatan, 2024)
The purpose of study were to analyze the form of legal protection for doctors for the occurrence of risks in telemedicine services to patients. A normative juridical method is used in this research in which the implementation of this method is a study of legal principles and legal systematics. This research was a normative legal research. The results showed that the form of legal protection for doctors against risks in telemedicine services to patients is in the form of preventive and repressive protection. Legal protection for doctors in therapeutic relationships of health services through electronic telemedicine media is regulated in Law Number 17 of 2023 concerning Health. Preventive legal protection is preventive in nature against disputes, where in this case the KKI organizes training and skills improvement activities for doctors in order to improve the quality of services provided to patients. On the other hand, the protection provided is repressive legal protection related to the resolution of medical disputes between medical personnel and patients.Abstrak: Tujuan penelitian ini adalah untuk menganalisis bentuk perlindungan hukum bagi dokter atas terjadinya risiko dalam pelayanan telemedicine kepada pasien. Penelitian ini termasuk penelitian normative yuridis. Hasil penelitian menunjukkan bahwa bentuk perlindungan hukum bagi dokter atas terjadinya risiko dalam pelayanan telemedicine kepada pasien adalah dalam bentuk perlindungan yang bersifat preventif maupun represif. Perlindungan hukum terhadap dokter dalam hubungan teraupeutik pelayanan kesehatan melalui media elektronik telemedisin diatur dalam Undang-Undang Nomor 17 Tahun 2023 Tentang Kesehatan. Perlindungan hukum preventif bersifat pencegahan atas terjadinya sengketa, dimana dalam hal ini KKI menyelenggarakan pelatihan dan kegiatan peningkatan keterampilan bagi dokter agar dapat meningkatkan mutu pelayanan yang diberikan kepada pasien. Di sisi lain perlindungan yang diberikan adalah perlindungan hukum represif yang berkaitan dengan penyelesaian sengketa medis antara tenaga medis dengan pasien